2001
DOI: 10.1111/j.1749-6632.2001.tb03791.x
|View full text |Cite
|
Sign up to set email alerts
|

Perifollicular Vascularity and Its Relationship with Oocyte Maturity and IVF Outcome

Abstract: New markers of embryo ability to implant are pursued continuously. Understanding whether an oocyte is really "mature," that is, ready to be fertilized, would be of great help in choosing an embryo that will implant. It is usual to pay attention to the phase of meiosis, considering the extrusion of the polar body (metaphase II) to be the only sign of the maturity of the oocytes. Nevertheless, understanding more about how the cytoplasm contributes to an oocyte's competency also shows promise as a method of predi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
41
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 50 publications
(45 citation statements)
references
References 11 publications
(19 reference statements)
2
41
0
1
Order By: Relevance
“…The significantly higher proportion of large follicles with high grade PFBF in the late follicular phase and significantly higher clinical pregnancy rate in "good beginners" in our study indirectly shows the association between a high grade PFBF in the late follicular phase with a high clinical pregnancy rate, confirming the findings of the other PDU studies (5)(6)(7). This study also demonstrated that the mean number of oocytes retrieved was significantly higher in "good beginners" compared to "poor beginners," supporting the findings by Bhal et al (6).…”
Section: Discussionsupporting
confidence: 91%
See 3 more Smart Citations
“…The significantly higher proportion of large follicles with high grade PFBF in the late follicular phase and significantly higher clinical pregnancy rate in "good beginners" in our study indirectly shows the association between a high grade PFBF in the late follicular phase with a high clinical pregnancy rate, confirming the findings of the other PDU studies (5)(6)(7). This study also demonstrated that the mean number of oocytes retrieved was significantly higher in "good beginners" compared to "poor beginners," supporting the findings by Bhal et al (6).…”
Section: Discussionsupporting
confidence: 91%
“…The information on proportion of grade 3 and 4 was not available in the PDU study by Borini et al (7). The most likely explanation for this difference in the proportion of grade 3 and 4 follicles between the present study and the other studies is that the ovarian PFBF in the above cited studies(5-7) was assessed on the day of egg pick up (approximately 32-34 h following hCG administration) compared to all PFBF assessments being performed prior to the hCG trigger in our study.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Therefore, since it is a non invasive technique and with reliable application, it is a useful tool to target new reproductive diagnoses. The evaluation of perifollicular vascularity was done in cows (Siddiqui et al 2008), women (Coulam et al 1999, Bhal et al 2001, Borini et al 2001, and mares (Silva et al 2006), and in all of these species was detected greater vascularity in the preovulatory follicle wall in individuals that became pregnant after mating.…”
Section: Introductionmentioning
confidence: 99%